PENGARUH MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR IPA MATERI PERUBAHAN WUJUD BENDA DI SD - Imelda Uneputty; Dominggus Rumahlatu; Johanes Pelamonia; Eka Sriwahyuni (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Science learning on the material of changes in the state of matter in fourth grade is often considered abstract and boring due to the dominance of lecture methods, resulting in low student learning outcomes. This study aims to determine the effect of using pop-up book learning media on the science learning outcomes of fourth-grade students at SD Negeri 61 Ambon. This study employed a quantitative approach with a one group pretest-posttest design. The population and sample consisted of all 23 fourth-grade students at SD Negeri 61 Ambon. The sampling technique used total sampling (saturated sampling), in which all members of the population were included as research participants. Data were collected using tests in the form of pretest and posttest, as well as observation. Data analysis included descriptive analysis, normality test, homogeneity test, Paired Sample T-Test, and N-Gain analysis. The results showed that the students' average pretest score was 51.85 and increased to 69.67 in the posttest. The Paired Sample T-Test produced a significance value of 0.000 < 0.05, indicating a significant difference in learning outcomes before and after the treatment. Furthermore, the N-Gain analysis yielded an average score of 0.4020, categorized as moderate. Therefore, the use of pop-up book media had a significant effect on improving science learning outcomes on the material of changes in the state of matter among fourth-grade students at SD Negeri 61 Ambon. The pop-up book media helps transform abstract concepts into more concrete and visual representations, thereby supporting students' understanding and engagement during the learning process. ABSTRAK Pembelajaran IPA materi perubahan wujud benda di kelas IV SD sering kali dianggap abstrak dan membosankan karena dominasi metode ceramah, sehingga berdampak pada rendahnya hasil belajar siswa. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran pop-up book terhadap hasil belajar IPA materi perubahan wujud benda pada siswa kelas IV SD Negeri 61 Ambon. Penelitian ini menggunakan pendekatan kuantitatif dengan desain one group pretest-posttest design. Populasi sekaligus sampel penelitian adalah seluruh siswa kelas IV SD Negeri 61 Ambon yang berjumlah 23 siswa. Teknik pengambilan sampel menggunakan total sampling (sampel jenuh), yaitu seluruh anggota populasi dijadikan sebagai sampel penelitian. Teknik pengumpulan data menggunakan tes berupa pretest dan posttest serta observasi. Analisis data meliputi analisis deskriptif, uji normalitas, uji homogenitas, Paired Sample T-Test, dan uji N-Gain. Hasil penelitian menunjukkan bahwa rata-rata nilai pretest siswa sebesar 51,85 meningkat menjadi 69,67 pada posttest. Hasil Paired Sample T-Test menunjukkan nilai signifikansi sebesar 0,000 < 0,05, yang berarti terdapat perbedaan yang signifikan antara hasil belajar sebelum dan sesudah diberikan perlakuan. Selain itu, hasil uji N-Gain memperoleh nilai rata-rata sebesar 0,4020 dengan kategori sedang. Dengan demikian, penggunaan media pop-up book berpengaruh signifikan terhadap peningkatan hasil belajar IPA materi perubahan wujud benda pada siswa kelas IV SD Negeri 61 Ambon. Media pop-up book membantu mengubah konsep yang bersifat abstrak menjadi lebih konkret dan visual sehingga dapat mendukung pemahaman serta keterlibatan siswa dalam proses pembelajaran.